Elevated expression of long intergenic non‐coding RNA HOTAIR in a basal‐like variant of MCF‐7 breast cancer cells. Issue 12 (18th October 2014) - Zhuang, Yan; Nguyen, Hong T.; Burow, Matthew E.; Zhuo, Ying; El‐Dahr, Samir S.; Yao, Xiao; Cao, Subing; Flemington, Erik K.; Nephew, Kenneth P.; Fang, Fang; Collins‐Burow, Bridgette; Rhodes, Lyndsay V.; et al.
<x xml:space="preserve">Abstract</x> Epigenetic regulation of gene expression is critical to phenotypic maintenance and transition of human breast cancer cells. HOX antisense intergenic RNA (HOTAIR) is a long intergenic non‐coding RNA that epigenetically represses gene expression via recruitment of enhancer of zeste homolog 2 (EZH2), a histone methyltransferase. Elevated expression of HOTAIR promotes progression of breast cancer. In the current study we examined the expression and function of HOTAIR in MCF‐7‐TNR cells, a derivative of the luminal‐like breast cancer cell line MCF‐7 that acquired resistance to TNF‐α‐induced cell death. The expression of HOTAIR, markers of the luminal‐like and basal‐like subtypes, and growth were compared between MCF‐7 and MCF‐7‐TNR cells. These variables were further assessed upon inhibition of HOTAIR, EZH2, p38 MAPK, and SRC kinase in MCF‐7‐TNR cells. When compared with MCF‐7 cells, MCF‐7‐TNR cells exhibited an increase in the expression of HOTAIR, which correlated with characteristics of a luminal‐like to basal‐like transition as evidenced by dysregulated gene expression and accelerated growth. MCF‐7‐TNR cells exhibited reduced suppressive histone H3 lysine27 trimethylation on the HOTAIR promoter. Inhibition of HOTAIR and EZH2 attenuated the luminal‐like to basal‐like transition in terms of gene expression and growth in MCF‐7‐TNR cells. Inhibition of p38 and SRC diminished HOTAIR expression and the basal‐like phenotype in MCF‐7‐TNR cells. HOTAIR was robustly expressed in the native basal‐like breast cancer cells and inhibition of HOTAIR reduced the basal‐like gene expression and growth. Our findings suggest HOTAIR‐mediated regulation of gene expression and growth associated with the basal‐like phenotype of breast cancer cells. © 2014 Wiley Periodicals, Inc.